Speech recognition in noise task among children and young-adults: a pupillometry study - Trau-Margalit, Avital; Fostick, Leah; Harel-Arbeli, Tami; Nissanholtz-Gannot, Rachel; Taitelbaum-Swead, Riki (Frontiers in Psychology, 2023)
Introduction Children experience unique challenges when listening to speech in noisy environments. The present study used pupillometry, an established method for quantifying listening and cognitive effort, to detect temporal changes in pupil dilation during a speech-recognition-in-noise task among school-aged children and young adults. Methods Thirty school-aged children and 31 young adults listened to sentences amidst four-talker babble noise in two signal-to-noise ratios (SNR) conditions: high accuracy condition (+10 dB and + 6 dB, for children and adults, respectively) and low accuracy condition (+5 dB and + 2 dB, for children and adults, respectively). They were asked to repeat the sentences while pupil size was measured continuously during the task. Results During the auditory processing phase, both groups displayed pupil dilation; however, adults exhibited greater dilation than children, particularly in the low accuracy condition. In the second phase (retention), only children demonstrated increased pupil dilation, whereas adults consistently exhibited a decrease in pupil size. Additionally, the children’s group showed increased pupil dilation during the response phase. Discussion Although adults and school-aged children produce similar behavioural scores, group differences in dilation patterns point that their underlying auditory processing differs. A second peak of pupil dilation among the children suggests that their cognitive effort during speech recognition in noise lasts longer than in adults, continuing past the first auditory processing peak dilation. These findings support effortful listening among children and highlight the need to identify and alleviate listening difficulties in school-aged children, to provide proper intervention strategies.